Assessment of the Potential of Sarcandra glabra (Thunb.) Nakai. in Treating Ethanol-Induced Gastric Ulcer in Rats Based on Metabolomics and Network Analysis - Li, Chao; Wen, Rou; Liu, DeWen; Yan, LiPing; Gong, Qianfeng; Yu, Huan (Frontiers in Pharmacology, 2022)
Gastric ulcer (GU) is one of the most commonly diagnosed diseases worldwide, threatening human health and seriously affecting their quality of life. Reports have shown that the Chinese herbal medicine, Sarcandra glabra (Thunb.) Nakai (SGN) can treat GU. However, its efficacy deserves further validation. Besides, its mechanism for treating GU is unclear. In order to assess the gastroprotective effect of SGN and systematically determine its mechanism underlying GU treatment. An acute gastric ulcer (AGU) rat model induced by alcohol was used to evaluate the gastroprotective effect of SGN by analysis of the histopathological changes of stomach tissue and related cytokine levels, and the potential mechanisms of SGN were investigated with serum metabolomics and network pharmacology. Differential metabolites of rat serum were identified by metabolomics, the metabolic pathways of the identified metabolites were enriched via MetaboAnalyst. afterwards, the critical ingredients and candidate targets of SGN anti-AGU were found out. A compound-reaction-enzyme-gene network was established by Cytoscape software version 3.8.2 based on integrated analysis of metabolomics and network pharmacology. Finally, molecular docking was applied to verify the acquired key targets. The results showed that SGN had a certain protective effect on GU via multiple pathways and targets. Mainly through the key active ingredients of isofraxidin, rosmarinic, caffeic acid to regulate hub targets, such as PTGS2, MAPK1, KDR that further to maintain the homeostasis of related metabolites. Signal pathways involved energy metabolism, immune and amino acid metabolism. Overall, the multi-omics techniques as promising tools to illuminate the mechanism of action of Chinese medicine in protecting from diseases, this integrated strategy provides a basis for further research and clinical application of SGN.